Analgesic antipyretic drugs as antagonists of bradykinin - Collier, H. O. J. (1960)
The antagonism between analgesic antipyretic drugs and bradykinin was examined quantitatively, using the bronchoconstrictor response of guinea-pigs in vivo. The dose of bradykinin required to overcome antagonism by calcium acetylsalicylate increased with the dose of acetylsalicylate given, the ratio being roughly constant. Fifty times the quantity of acetylsalicylate which just antagonized bradykinin did not modify bronchoconstriction due to small doses of histamine, 5-hydroxytryptamine, or acetylcholine. A method of measuring the potency of this anti-bradykinin action was developed. Acetylsalicylic acid, phenylbutazone, amidopyrine, and phenazone had a high potency; paracetamol, cinchophen, sodium salicylate, and acetanilide had a moderate potency; and phenacetin, salicylamide, and 4-hydroxyisophthalic acid had little or none. Cortisone, hydrocortisone, aldosterone, amodiaquine, and morphine were ineffective or their action was non-specific. In sensitized guinea-pigs, an injection of antigen caused bronchospasm. This response was greatly lessened by pretreatment with mepyramine, but was not affected by calcium acetylsalicylate, lysergic acid diethylamide, or atropine. Acetylsalicylic acid, phenylbutazone, and amidopyrine did not specifically antagonize the action of bradykinin on the capillaries of guinea-pig skin in vivo, on guinea-pig ileum in vitro or on rat duodenum in vitro.